OPTIMISING PROFITABILITY: THE ROLE OF DPK, COF, AND LIQUIDITY ON THE SUSTAINABILITY OF ISLAMIC BANKS - Rudiatna, Talitha Dwi Yumna; Yahya, Alvin (NISBAH: Jurnal Perbankan Syariah, 2024)
Third party funds are a source of funds for the bank in channeling it back to the community in the form of loans or financing, third party funds collected by the bank will return to the community with a difference in the ratio / profit sharing and / or margin in accordance with the agreed agreement, thus causing Cost of Fund for the bank against the third party funds. Apart from that, these third party funds can be taken at any time by customers in accordance with their deposit products so that banks are required to maintain and guarantee financial liquidity both in the long, medium and short term. Banks as an industry also focus on profitability so that one of the goals is to generate profits or profits. In this study the author carries out financial report analysis to see the level of value of each variable including third party funds, cost of funds and liquidity. The method used in this study is to use a sample from financial reports of Bank Syariah Indonesia with financial reports presented monthly from 2021-2024. The analysis test is used to be able to see how much influence on each variable using descriptive tests, classical assumptions, and multiple linear regression. The test results that have been carried out present data that Third Party Funds (DPK), Cost Of Fund (COF), have positive significant results on Profitability. While the results of the liquidity variable proxied by the current ratio are not positively significant to profitability at Bank Syariah Indonesia (BSI) with the period 2021-2024.